Rules-Based Optimal Mitigation of Economic Uncertainty - Pei-Tha Gan,; Kian-Teng Kwek, (Asian Academy of Management Journal of Accounting and Finance, 2023)
A notable attribute of the empirical studies on monetary rules is that few published articles rely on the normative evaluation in eliminating unwanted economic uncertainty. To prevail over this shortcoming, this paper introduces the optimal mitigation of economic uncertainty and determines its applicability through a sample of 14 selected countries. Using the combination of the theoretically derived optimal mitigation of economic uncertainty with the empirical estimations leads to specific monetary rules. The findings of this paper provide some policy implications; the optimal mitigation of economic uncertainty can characterise the optimal use of the interest rate and exchange rate to eliminate economic uncertainty and serve as a monetary policy guide in the adjustment process to restore macroeconomic conditions of the equilibrium that eventually promote the best macroeconomic outcomes.